2020
DOI: 10.5713/ajas.19.0050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Macleaya cordata and Magnolia officinalis plant extracts on oxidative stress control in lambs fed a high-concentrate diet

Abstract: Objective: The objective of this experiment was to compare conventional antioxidants and plant extracts for oxidative stress control in lambs fed a high-concentrate diet.Methods: Forty-eight male Dorper×Santa Ines lambs with an initial weight of 20±1.49 kg and 60 days of age, were used to evaluate the effects of feeding a combination of <i>Macleaya cordata</i> and <i>Magnolia officinalis</i> plant extracts (0 vs 320 mg/kg dry matter [DM]) in combination with selenium+vitamin E (0 vs 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This includes antimicrobial and anthelminthic properties [ 33 ]. Moreover, other experiments in sheep have observed that Macleaya cordata extracts reduce oxidative stress [ 34 ], including in heat-stressed animals where improvements in feed conversion efficiency were observed [ 35 ]. Isoquinoline alkaloids are widely reported to have anti-inflammatory properties [ 31 , 36 ], with the effect at least partially mediated via changes in NF- k β [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This includes antimicrobial and anthelminthic properties [ 33 ]. Moreover, other experiments in sheep have observed that Macleaya cordata extracts reduce oxidative stress [ 34 ], including in heat-stressed animals where improvements in feed conversion efficiency were observed [ 35 ]. Isoquinoline alkaloids are widely reported to have anti-inflammatory properties [ 31 , 36 ], with the effect at least partially mediated via changes in NF- k β [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the changes in DMI, ADG and ADG: DMI remained unaffected by MCE ( p = 0.68). Previous research [ 11 , 17 , 18 , 19 ] also does not show an impact of feeding MCE on the ADG of ruminants. On the other hand, feeding MCE seems to influence individual tissue development and thus the carcass composition of cattle [ 11 ].…”
Section: Resultsmentioning
confidence: 72%
“…High‐concentrate diets can interfere with the metabolism of ruminants, resulting in the release of diverse compounds into the blood circulation and affecting the redox homoeostasis of the animal (Lima et al, 2020). Additionally, prolonged feeding of a high‐concentrate diet can lead to ruminal and intestinal microbial metabolism disorders and gastrointestinal epithelial inflammation damage and can further aggravate oxidative stress.…”
Section: Discussionmentioning
confidence: 99%